Patients with alcohol‐related liver disease – beliefs about their illness and factors that influence their self‐management. (8th October 2015) - Lau‐Walker, Margaret; Presky, Jonathan; Webzell, Ian; Murrells, Trevor; Heaton, Nigel
Abstract: Aim: To determine the association between illness belief and self‐efficacy to provide the evidence‐base to develop a personalized framework to support self‐management in patients with alcohol‐related liver disease. Background: Research in a variety of long‐term illnesses suggests patients' illness beliefs are a more influential factor for patient recovery than the severity of the illness. However, research into illness belief and self‐efficacy of patients with alcohol‐related liver disease is sparse. Design: A cross‐sectional survey. Methods: A cohort of 159 patients with alcohol‐related liver disease who attended the Liver Outpatient Clinics at a London Hospital (October 2012–November 2013) completed a set of validated instruments measuring illness beliefs, self‐efficacy, emotional states and quality of life. Findings: The mean age of enrolled patients was 52 years, 67% male, 26% live on their own, 61% had no previous history of other chronic illness and average Model for End‐Stage Liver Disease and The AUDIT Alcohol Consumption Questions scores were 11·0 and 3·5 respectively. After adjusting for demographic and illness characteristic components, multiple regression analysis shows that the three illness belief components 'Symptoms', 'Understanding' and 'Concerns' made a significant contribution to their confidence to self‐manage their liver condition and the 'Symptoms' component makes a signification contribution across to all outcome measures: Anxiety, Depression, Quality of Life and Self‐Efficacy. Conclusion: Interventions designed to improve these patients' understanding of their illness and strategies to manage their symptoms are likely to improve their self‐management, quality of life and reduce anxiety and depression.